Sémiotisation et littérarisation de la focalisation dans le roman Bleu-Blanc-Rouge d’Alain Mabanckou - Aboubakar Gounougo (Multilinguales)
In Alain Mabanckou’s novel Bleu-Blanc-Rouge, focusing is a semiotic which can be understood through the pragmatics of an "I-me-narrator" who tells of his presence in the world. Narration in fact acquires its literarity by the intersection of discursive facts of extra and intra diegetic with those of the diegetic to construct the rhythmic narrative of a mundane offered for meditation.